The socialist way of life in Siberia : transformation in Buryatia - Chakars, Melissa (Central European University Press, 2014)
The Socialist Way of Life in Siberia presents the dramatic late twentieth century transformation in the everyday lives of the Buryats, a Mongolian people who live in Siberian Russia. The book challenges the common perception that the process of modernization during the later Soviet period created national assertiveness rather than assimilation or support for the state. The author examines the central question of being a Buryat and being a successful Buryat in the socio-political structures of the Tsarist Russian Empire, later during Socialism and in present-day Russia. The Buryats and especially the intellectual elite of the Buryats are treated as a group which due to their historical and cultural roots and capability (determined also historically) became an integral and efficient part of the Russian administrative and cultural life. By 1991, the Buryats were overrepresented in nearly every profession in their autonomous republic despite the fact that they made up only around 25 percent of its population.